Detection of major histocompatibility complex class II gene on sowang giant gourami (Osphronemus goramy Lacepede, 1801) fingerling from one spawning - Kusbiyanto Kusbiyanto; Agus Nuryanto; Petrus Hary Tjahja Soedibja (Jurnal Iktiologi Indonesia, 2016)
The fish farmer belief that strain sowang of giant gourami has the high growth rate. Nevertheless, the culture of this strain was constrained by high mortality due to low resistance to Aeromonas hydrophila infection. Resistance is a genetically inherited character from their parents. Resistant brood stock can be obtained through selection using molecular marker that is associated with resistance, such as major histocompatibility complex class II (MHC II) gene. At first step, detection of MHC II gene on sowang strain needs to be done. The aims of this study were 1) to detect the presence of the MHC II gene on sowang strain and 2) to analyze the resistance level of sowang strain from one spawning. A total of 100 individuals of sowang strain fingerling was infected with 0.1 ml 108 CFU of A. hydrophila. Genomic DNA was isolated using the thermoscienstific DNA easy kit and the fragmen of MHC II gene was amplified using two different primer pairs of stickleback fish. The presence of the MHC II gene was defined based on DNA band appearance on agarose gel, while resistance level was analyzed descriptively based on the total number of death and live individuals after infection. Amplification of the MHC II gene using the second primer pair from death individuals results in approximately of 400 bp fragment. However, MHC II gene amplification from living individuals resulted of approximately of 400 bp and 585 bp length of DNA fragments. The 585 bp fragment of the MHC II gene is a specific molecular marker for sowang giant gourami strain which is resitant to A. hydrophila infection. A total of 71% fingerling was death and 29% of fingerling was survived. This proved that the fingerling from one spawning have different resistance characteristic. Abstrak Petani ikan percaya bahwa ikan gurami ras sowang memiliki laju pertumbuhan yang tinggi. Namun budi daya ras tersebut terkendala oleh kematian yuwana yang tinggi akibat rendahnya resistensi terhadap infeksi Aeromonas hydrophila. Resistensi merupakan sifat yang diwariskan oleh induk ke anakan. Induk resisten dapat diperoleh melalui seleksi menggunakan penciri molekuler terkait dengan sifat resisten, seperti Major Histocompatibility Complex kelas II (MHC II). Sebagai langkah awal, perlu dilakukan deteksi keberadaan gen MHC II pada yuwana gurami sowang. Tujuan penelitian ini adalah 1) mendeteksi keberadaan gen MHC II pada yuwana gurami sowang dan 2) menganalisis tingkat resistensi yuwana ikan gurami sowang yang berasal dari satu pemijahan. Sebanyak 100 ekor ikan diinfeksi mengguna- kan 0,1 ml bakteri Aeromonas hydrophila dengan kepadatan koloni 108 CFU. DNA diisolasi menggunakan Thermo- scienstific DNA easy kit dan gen MHC II dimplifikasi menggunakan dua pasang primer dari ikan stickleback. Data yang diperoleh dianalisis secara deskriptif. Keberadaan gen MHC II ditentukan berdasarkan kemunculan pita DNA pa- da gel agarosa, sedangkan tingkat resistensi ditentukan berdasarkan jumlah ikan yang mati dan hidup pascainfeksi. Am- plifikasi gen MHC II dari individu yang mati menghasilkan fragmen DNA sepanjang 400 bp. Namun, amplifikasi gen MHC II dari individu yang tetap hidup pascainfeksi menghasilkan fragmen DNA sepanjang sekitar 400 pb dan 585 bp. Fragmen gen MHC II berukuran sekitar 585 bp merupakan marka molekuler spesifik untuk gurami sowang tahan infek- si A. hydrophila. Sebanyak 71% ikan mati dan 29% hidup setelah 14 hari pascainfeksi. Hasil tersebut membuktikan bahwa yuwana gurami sowang memiliki resistensi berbeda terhadap Aeromonas hydrophila.